1989
DOI: 10.2307/3350224
|View full text |Cite
|
Sign up to set email alerts
|

Spouses and Children of Disabled Elders: How Large a Constituency for Long-Term Care Reform?

Abstract: Over 13 million adults in the United States have disabled elderly parents or spouses and are potential providers of long-term care, financial assistance, or emotional support. Articles in the popular press notwithstanding, data from the 1984 National Long-term Care Survey indicate that a relatively small number of adult children and spouses assume the multiple responsibilities of elder care and child care or employment. These individuals form a subset of a much larger group of 4.2 million persons, however, who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

1994
1994
2009
2009

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(25 citation statements)
references
References 14 publications
1
23
0
1
Order By: Relevance
“…The score for involvement in household tasks was consistently higher for older women than older men across all study variables (see Table 4). Similar to what has been previously published on the effect of household size on older adults' contribution to domestic labor (Stone and Kemper 1990), our results showed that older women were less involved in household tasks in larger households (score = 23.6 in households with 7+ members, while score = 37.4 in households with 2-6 members). The higher the educational level of older men and women, the higher was their participation in household tasks.…”
Section: Factors Affecting Older Adults' Involvement In Domestic Laborsupporting
confidence: 91%
“…The score for involvement in household tasks was consistently higher for older women than older men across all study variables (see Table 4). Similar to what has been previously published on the effect of household size on older adults' contribution to domestic labor (Stone and Kemper 1990), our results showed that older women were less involved in household tasks in larger households (score = 23.6 in households with 7+ members, while score = 37.4 in households with 2-6 members). The higher the educational level of older men and women, the higher was their participation in household tasks.…”
Section: Factors Affecting Older Adults' Involvement In Domestic Laborsupporting
confidence: 91%
“…We have further adjusted these weights to be consistent with the Census Bureau definitions of institutional residence. Differences in our 1984 estimates relative to similar estimates appearing in Stone and Kemper (1989) are the result of slightly different weighting. We reestimated all 1984 numbers to ensure consistent methodology across the two years.…”
Section: Analytic Methodsmentioning
confidence: 62%
“…Spouses and children are the majority of active informal caregivers to disabled elders. Three-fifths of the 7.3 million active informal caregivers in 1984 were spouses or children of the care recipient (Stone and Kemper 1989). That proportion had increased to two-thirds by 1994 (Spector, Fleishman, Pezzin, et al 1998).…”
Section: Samplementioning
confidence: 99%
See 1 more Smart Citation
“…For example, contrary to the belief of some that family caregiving is declining, research on informal caregiving identified the extensive amount of LTC that family members not only have provided historically but continue to provide (Spillman & Pezzin, 2000;Stone, Cafferata, & Sangl, 1987;Stone & Kemper, 1989). This is not an isolated example.…”
Section: A Typology Of Research Contributionsmentioning
confidence: 95%